Research on the scientific connotation and practical path of the construction of sports power - Jiang, Bo; Wang, Shaojie (Quality in Sport, 2024)
This study takes Xijin Ping’s important discourse on the construction of a powerful sports country as the research object, mainly uses the literature method to comprehensively sort out and summarize the important speeches and discourse on the construction of a powerful sports country, extracts the main connotation and distinctive Chinese characteristics of Xijin Ping’s thought of a powerful sports country, and analyzes the formation and development process of his thought of a powerful sports country in multiple dimensions. The research holds that the scientific connotation of the construction of sports power includes: to carry forward the Chinese sports spirit and promote the nation’s spiritual strength; Young strong China strong, starting from the child, establish the concept of sports education; Strive to do a good job of "three big balls", insist on developing mass sports, and enhance the attributes of sports industry; Improve the country’s ability to host and participate in the competition, and build a new pattern of foreign sports exchanges and cooperation; Take the national fitness as the starting point to promote the people’s physical fitness from the overall strong five aspects. Research objectives: On the basis of a deep understanding of the scientific connotation, adhere to the strategic deployment of sports power, identify the focus of sports reform, innovate the concept of sports development, and strive to promote the coordinated development of competitive sports, national fitness, and sports industry, so as to achieve the goal of building a world sports power. ​